2009
DOI: 10.1089/neu.2009.0961
|View full text |Cite
|
Sign up to set email alerts
|

Spreading Depolarizations and Late Secondary Insults after Traumatic Brain Injury

Abstract: Here we investigated the incidence of cortical spreading depolarizations (spreading depression and peri-infarct depolarization) after traumatic brain injury (TBI) and their relationship to systemic physiologic values during neurointensive care. Subdural electrode strips were placed on peri-contusional cortex in 32 patients who underwent surgical treatment for TBI. Prospective electrocorticography was performed during neurointensive care with retrospective analysis of hourly nursing chart data. Recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(87 citation statements)
references
References 44 publications
(61 reference statements)
3
83
1
Order By: Relevance
“…On the other hand, pannexin hemichannels could be activated during conditions of cellular depolarization such as traumatic brain injury [43], stroke [44] and subarachnoid hemorrhage [45]. Under normal conditions, Panx1 could contribute to the propagation of calcium waves within the vasculature by mediating the release of ATP [18] and as such play an important role in mediating vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pannexin hemichannels could be activated during conditions of cellular depolarization such as traumatic brain injury [43], stroke [44] and subarachnoid hemorrhage [45]. Under normal conditions, Panx1 could contribute to the propagation of calcium waves within the vasculature by mediating the release of ATP [18] and as such play an important role in mediating vascular tone.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have found worse outcomes in patients whose electrocorticography recordings showed the occurrence of CSD following the inciting trauma. Moreover, the presence of CSD correlated with low blood pressure, abnormal cerebral pressure, and fever, all of which have been associated with increased morbidity in trauma patients [23]. …”
Section: Neuronal Injury Leading To Csdmentioning
confidence: 99%
“…The long-term functional significance of this surprising lability of dendritic spine morphology to cognitive function, and future susceptibility to a range of pathologies from Alzheimer's to epilepsy to migraine, is unknown. However, it seems a reasonable hypothesis that the complete recovery of spine size at their former locations following SD that is promoted by GLYX-13 is likely to be therapeutically beneficial in preventing long-term negative sequelae of migraine, and other generators of SDs such as traumatic brain injury (Hartings et al, 2009(Hartings et al, , 2014Sword et al, 2013), ischemia (Risher et al, 2010) and seizures (Takano et al, 2007).…”
Section: Discussionmentioning
confidence: 99%